Merdeka Belajar: Akselerasi Pembelajaran Sesuai Bakat dan Minat - Resti Ramdayani; Masduki Asbari; Erisha Nurfatimah (Journal of Information Systems and Management (JISMA), 2023)
The aim of this discussion is to ensure that every student has access and the opportunity to learn according to their interests and potential, so that they can achieve optimal learning outcomes and contribute to the development of themselves, society and the country as a whole. This study report uses a descriptive qualitative method by taking notes because the data source was obtained by listening to oral narratives from the channel The Ministry of Education and Culture's YouTube entitled "Expanding Learning Opportunities for Students According to Their Interests and Potential" is presented by him. The results of this study explain the effectiveness of various approaches and strategies in expanding learning opportunities for pupils and students according to their interests and potential. This includes understanding the positive impact of an inclusive approach on student motivation, engagement and learning outcomes, as well as how implementing policies that support individual interests and potential can create a more adaptive and relevant educational environment. The study may also include findings regarding factors that support or hinder the implementation of these practices in educational contexts.